THE EFFECTIVENESS TEST OF CIPLUKAN (Physalis angulate L.) LEAF EXTRACT ON WOUND HEALING IN MALE RABBIT (Oryctolagus cuniculus) WISTAR STRAIN - Baiq Mahmudah; Recta Olivia Umboro; Fitri Apriliany (STIKES Cendekia Utama Kudus, 2021)
An incision wound is a wound that occurs because of a sharp incision on the skin. This wound can occur in the dermis and epidermis of the skin with a depth 0,3cm, and length of 1,5cm. If not handle properly, the cut can develop into an infected wound. Ciplukan leaves (Physialis angulata L.) contain tannins compounds. Tanin compound can accelerate wound healing with cellular mechanism. The purpose of this study is to determine the ability of ciplukan leaves extract as an alternative medicine in healing the incisions.This study is an experimental study using a completely randomized design wich using 3 treatment groups of male rabbit (Oryctolagus cuniculus) consisted of: 1st group negative control (vaselin flava), 2nd group positive control (povidone iodine), 3rd group ciplukan leaves extract test with 3 different concentrations (15%, 30%, 45%). Wound healing was observed for 20 days.The results of the analysis using One-way ANOVA, Kruskal Wallis obtained a value of p?0.05, showed the extract of ciplukan leaves is effective in healing incisions . The healing ability equivalent to positive control with a healing time of 13 days was shown at a concentration of 45%.